2006
DOI: 10.1021/ol0517168
|View full text |Cite
|
Sign up to set email alerts
|

First Optically Active Molecular Electronic Wires

Abstract: [structure: see text]. The optically active molecular electronic wires (S)- and (R)-7 containing an oligo-arylene-ethynylene structure and a chiral 1,1'-binaphthyl unit are synthesized. These molecules are incorporated into nanowell devices by self-assembly on the gold surface. In the nanowell devices, the median currents from the molecules containing both S and R enantiomers are significantly smaller than those from the pure S or R molecule. Compounds (R)- and (S)-7 are also less conductive than the fully con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…[57][58][59] Previously, it was found that BINOL could be specifically brominated at the 6,6 0 -positions to give the corresponding chiral product 6,6 0 -dibromo-2,2 0 -binaphthol with 2.0 equiv of bromine. [48][49][50][51][52] According to reports by Li and Pu, [48,60,61] 4,4 0 ,6,6 0 -tetrabromo-2,2 0 -binaphthol could be directly synthesized with an excess amount of bromine. The bromination substitution, however, could take place at the 4,4 0 -positions while the 6,6 0 -positions of BINOL were occupied by chlorine atoms and the BINOL's hydroxyl groups were etherized by ethyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…[57][58][59] Previously, it was found that BINOL could be specifically brominated at the 6,6 0 -positions to give the corresponding chiral product 6,6 0 -dibromo-2,2 0 -binaphthol with 2.0 equiv of bromine. [48][49][50][51][52] According to reports by Li and Pu, [48,60,61] 4,4 0 ,6,6 0 -tetrabromo-2,2 0 -binaphthol could be directly synthesized with an excess amount of bromine. The bromination substitution, however, could take place at the 4,4 0 -positions while the 6,6 0 -positions of BINOL were occupied by chlorine atoms and the BINOL's hydroxyl groups were etherized by ethyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…1, top) [1] or polyaromatic ring (Fig. 1, bottom) [2]. Relatively short species, like those presented, allow an obvious geometrical control on the molecular shape that is suitable for single molecule studies by break-junction techniques.…”
Section: Covalent Wiresmentioning
confidence: 87%
“…These “alligator-clips” [1517] are able to bind functional molecules covalently to gold{111}-surfaces. Phenyl derivatives [1819], conjugated bi- [18,20] and oligophenyls [18,2021], oligothiophenes [18], porphyrin derivatives [20], phenanthrenes [2223], fullerenes [24], and optically active naphthalenes [25] adsorbed on gold were studied in break-junction experiments and their properties on conductance, 1-bit random access memory and, especially, with regard to their ability to function as conductive molecular wires investigated. Among many heteroaromatic systems, phenothiazines, their derivatives and oligomers are interesting building blocks for rigid-rod and wire-like molecular modules for single-molecule electronics as a consequence of their electronic properties.…”
Section: Introductionmentioning
confidence: 99%